ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI PT MATAHARI (STUDI KASUS HYPERMART SKA) - Putri, Asri Neli; Daulay, Hendry Yanto; Suparmi, Suparmi; Gustina, Putri (Postgraduate Management Journal, 2024)
The aim of this research is to analyze the factors that influence consumer purchasing decisions at PT Matahari Putra Prima (Hypermart SKA). The type of research carried out is descriptive research with a quantitative approach. Research variables consist of product quality, price and promotion. The population in this study were customers at Hypermart SKA Pekanbaru and the sampling technique used the accidental sampling method. The sample obtained was 96 people. The data analysis used is multiple linear regression analysis. Based on the results of the table above, it is known that the product quality variable has a t table value of 2.365 and a calculated t of 5.529 with a significance value of 0.000. The calculation results show that the calculated t is greater than the t table or 5.529 > 2.365 and the significance level is 0.000 < 0.050. The significance level is smaller than 0.05, which means that the hypothesis in this study is significant. Thus, the product quality hypothesis has a positive and significant effect on purchasing decisions.